PENGARUH BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP SEMANGAT KERJA PEGAWAI PADA DINAS PERHUBUNGAN KOTA BIMA - Mukhlis; Nurhidayanti; Yusuf, Muhammad (Jurnal Nusa Manajemen, 2024)
This research aims to determine the influence of organizational culture and work discipline on the work spirit of Bima City Transportation Department employees. The approach used in the research is an associative approach. The population in the study was 188 people with a sample of 32 ASN people. The data collection techniques used were observation, questionnaires and literature study. The data analysis techniques used were validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient, coefficient of determination, T test and F test which were processed using the Statistical Product and Service Solution (SPSS) version 20 program. that Organizational Culture and Work Discipline simultaneously have a significant effect on the Work Morale of Bima City Transportation Service Employees.